The Year 2000 from the Perspective of the People’s Party - Moroni, Sheyla (Populismo y propaganda: entre el presente y el pasado, 2020)
For a few years (1890–1896), the People’s Party was the “third party” of the United States and it changed the rhetoric of the two major parties into which it “dissolved” (especially in the case of the Democratic Party represented by William Jennings Bryan in 1896). The aim of the article is to test the political-narrative background which includes, among other productions in 1888, the first edition of Looking Backward. 2000–1887 by Edward Bellamy. One million copies of this book were sold and its readers created half a thousand nationalist clubs in the US. Caesar’s Column by Ignatius L. Donnelly’s (1890), author of the Preamble of the Party, was also widely sold.